Kebijakan Pemerintah Orde Baru dalam Meningkatkan Kompetensi Guru di Indonesia - Siti Utami Dewi Ningrum (Lembaran Sejarah, 2023)
This research explores the basis of policies to increase teacher competency in Indonesia during the New Order era. The research uses historical and bibliographical methods to explore official documents, mainly the statutory regulations and interviews with several teachers affected by the New Order government policies. This research found that the New Order government’s policy of increasing teacher competency could not be separated from the social, economic and political conditions at that time. Teachers, an essential element of education, are the object of policies to increase their competence. This research also shows that the New Order Government created legislative products as the basis for various strategic policies implemented for teachers in Indonesia to increase their competence.